RENEWAL OF THE NATIONAL CONTRACT LAW - Latifiani, Dian (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2020)
The development of transactions/contracts in Indonesia and the world is developing very rapidly. Meanwhile, Indonesian contract law is sourced from the Civil Code Book III. The Dutch colonial-made Burgerlijk Wetboek did not yet regulate national and international contracts which had undergone development. Indonesian values also do not exist in book III. So it is necessary to have contract law renewal based on the values of Pancasila. The problem discussed in this paper is how to reform the national contract law. The urgency for renewal is carried out to support the 2005-2025 National RPJP, namely